ECONOMIC SECURITY OF SUSTAINABLE DEVELOPMENT OF THE REPUBLIC OF UZBEKISTAN - Kaimova, Z.A; Kayimov, Tolibjon (International Conference on Business & Management, 2026)
This paper proposes a theoretical and methodological justification for ensuring economic security from the perspective of the impact of threats on the national economy. The conceptual provisions for ensuring economic security proposed in this work are aimed at strengthening the position and promoting the Republic of Uzbekistan on the global stage.